What Motivates Medical Students to Engage in Volunteer Behavior During the COVID-19 Outbreak? A Large Cross-Sectional Survey - Shi, Yu; Zhang, Shu-e; Fan, Lihua; Sun, Tao (Frontiers in Psychology, 2021)
fter the COVID-19 outbreak, the health status of the general population has suffered a huge threat, and the health system has also encountered great challenges. As critical members of human capital in the health sector, medical students with specialized knowledge and skills have positively fought against the epidemic by providing volunteer services that boosted the resilience of the health system. Although volunteer behavior is associated with individual internal motivation, there is sparse evidence on this relationship among medical students, especially regarding potential mechanisms. Therefore, this study had two main objectives: 1) to examine the influence of prosocial motivation of medical students on their volunteer behavior; and 2) to verify the chain-mediating role of calling and vocation as well as social responsibility in the relationship between prosocial motivation and volunteer behavior. Study Ӏ: a total of 2454 Chinese full-time medical students were invited to complete an online survey. Data analysis was performed using descriptive statistics, Pearson’s correlation coefficient, and multiple linear regression analysis. The results demonstrated that prosocial motivation significantly affected volunteer behavior in medical students (β=0.098, P<0.001); calling and vocation as well as social responsibility chain-mediated the relationship between prosocial motivation and volunteer behavior (β=0.084, P<0.001). Prosocial motivation promoted the formation of social responsibility by positively evoking calling and vocation of medical students, further resulting in increased volunteer behavior. Study Ⅱ: A 28 person qualitative interview was conducted. Qualitative data are added to reduce the limitations of online questionnaires. At the same time, we can also critically study the volunteer behavior of Chinese medical students during covid-19. The results showed that there were various reasons for medical students to volunteer in the process of fighting against covid-19, and the experience of volunteer service and the impact on their future life were different. Lastly, the current findings suggest that fostering volunteerism among medical students requires the joint effort of the government, non-profit organizations, and medical colleges.